2019
DOI: 10.3389/fenvs.2019.00156
|View full text |Cite
|
Sign up to set email alerts
|

Chemicals of Emerging Concern in Treated Wastewater Impact Microbial Growth

Abstract: Agriculture production in California is negatively impacted by soilborne fungi, such as Verticillium dahliae, and limited water availability for irrigation. Some regions have adapted the use of recycling wastewater, i.e., reclaimed water, to supplement the potable water supply. Wastewater purification is not fully efficient at removing all contaminants and small amounts of pharmaceutical products, known as chemicals of emerging concern (CECs), remain. Acetaminophen, trimethoprim, sulfamethoxazole and gemfibroz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…pH, salinity, organic load, heavy metal) 72 to minimize risks to human health and changes in soil properties 3 . The current study and many others [21][22][23][24][25][26] indicate that policies need to address the level of chemical contaminants, such as CECs, that may pose risks to natural and agricultural environments, thus indirectly affecting human health as well. Hopefully these policies will lead to the development of technology that can more effectively clean wastewater for reuse to such a degree that there will be no risk in using the invaluable source of water.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…pH, salinity, organic load, heavy metal) 72 to minimize risks to human health and changes in soil properties 3 . The current study and many others [21][22][23][24][25][26] indicate that policies need to address the level of chemical contaminants, such as CECs, that may pose risks to natural and agricultural environments, thus indirectly affecting human health as well. Hopefully these policies will lead to the development of technology that can more effectively clean wastewater for reuse to such a degree that there will be no risk in using the invaluable source of water.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, more studies on the impacts of CECs in RWW need to be conducted to ensure that this source of water does not have negative impacts on food and feed production. Our previous study 26 showed that CECs impact plant disease development, which may consequently affect food production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was originally believed that the final CEC concentrations in RWW effluent (typically in the μg to mg/L range) were too low to be biologically relevant [ 18 20 ]. However, recent evidence suggests that the concentrations of CECs in RWW can impact microorganisms, insects, and plants [ 21 26 ]. CECs accumulate in soils irrigated with RWW [ 14 ], and they are taken up by plants inevitably accumulating in their tissues [ 18 , 19 , 27 ].…”
Section: Introductionmentioning
confidence: 99%